Using Telecare to Treat Opioid Use Disorder: An Ethnographic Study in New York During COVID-19. (December 2021) - Caulfield, Christopher P.
This paper presents an in-person and digital ethnography of people in New York State who use drugs and seek treatment for opioid use disorder (OUD) using phone or video connection to receive healthcare (telecare) including interviews prior to and during the COVID-19 pandemic. This article leverages a Feminist and Science and Technology Studies (STS) approach to elucidate how the framing of the opioid crisis shapes the interconnections that are discernable, providing a heuristic to understand the increased rates of deaths due to drug overdose during the pandemic. The narratives of people seeking treatment are analyzed through the theoretical lenses of Nelly Oudshoorn's concept of the technogeography of care, Nancy Campbell's concept of technologies of suspicion, and Nancy Fraser's analysis of the US juridical-administrative-therapeutic in/justice system. This paper traces and problematizes how telecare contributes to redefining the experience of familiar places, such as home, into spaces of both care and surveillance, and how the technology of telecare presents both affordances and foreclosures to accessing care as people struggle to conform with its requirements in order to receive care. Key findings are, (1) the significance of hugs and tactile connection that is sorely missed by people using telecare for group therapy, (2) the critical importance of proximity to in-person services even while using telecare, (3) the resistance strategies of telecare users to surveillance mechanisms, and (4) the continued stigmatization of drug use and treatment acts as a key barrier to people who are striving to produce the identity of a patient who is clinically stable for take-home medication.